Integrated Water and Waste Management: A Systematic Literature Review on the Role of Human Resources and Sustainable Practices - Pangeran; Tomy Sun Siagian; Rizky Saputra; Dhea Agusty Ningrum; MHD. Andi Rasyid (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The growing pressure on water resources from urbanization, industrialization, and climate change demands an integrated and sustainable approach to water and waste management. This study explores the relationship between human dimensions, technology, and institutional governance in improving the effectiveness of sustainable water and waste management systems. The research addresses the limited studies that combine Green Human Resource Management (GHRM) practices, smart technology adoption, and adaptive institutional models such as Integrated Water Resources Management (IWRM) within one conceptual framework. This study develops an integrated conceptual model that explains the triadic relationship between green human resources as an enabler, digital technology as a driver, and collaborative governance as a bridge to effective water and waste systems. A Systematic Literature Review (SLR) guided by PRISMA 2020 was conducted using thematic synthesis and bibliometric analysis to identify trends, dominant theories, and relationships among key variables. The findings show that effective water and waste management depends not only on technological innovations such as AI, IoT, smart sensors, big data, and Life Cycle Assessment (LCA), but also on human readiness and institutional capacity. GHRM practices green recruitment, environmental training, and sustainability-based performance appraisals enhance technological adoption and promote an eco-conscious culture. Moreover, the expansion of IWRM into “IWRM extended to waste” emphasizes cross-sector collaboration and community engagement. Sustainable water and waste management can thus be achieved through synergy among humans, technology, and governance within an adaptive socio-technical system.